PERBANDINGAN FAKTOR YANG MEMPENGARUHI PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA UKM DI DESA DAN DI KOTA (STUDI KASUS USAHA UKM KABUPATEN REMBANG) - Rikah Rikah (STIE Pelita Nusantara Semarang, 2019)
This research aims to examine the effect of owner education, business scale, company age and accounting training on the use of accounting information. This research use survey method by using sample of Small Medium Enterprises (UKM) which is in Rembang Regency, sampling in this research is using cluster sampling with obtained research sample counted 120 UKM. 60 UKM from district around Rembang city, and 60 UKM others from district far from Rembang city. The analysis in this study used multiple linear regression analysis. The result of hypothesis show that owner education have positive effect to accounting information, business scale have no significant effect to accounting information, firm age have positive effect to accounting information, accountancy training have positive effect to accounting information.